Experimental study on detoxication effect of sulfhydryl compounds in acute poisoning of dimethylformamide - Lu, Zhong-Qiu (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2007)
OBJECTIVE: To study the change in oxidase and anti-oxidase in liver of the mice poisoned by dimethylformamide (DMF), and the effects of the treatment with sulfhydryl compounds in acute poisoning of DMF